2011
DOI: 10.1590/s0004-282x2011000100019
|View full text |Cite
|
Sign up to set email alerts
|

Study of the profile of the neurotrophin BDNF in new leprosy cases before, during and after multidrug therapy

Abstract: Brain-derived neurotrophic factor (BDNF) is a neurotrophin involved in the survival of neurons and growth and differentiation of dendrites and axons. The purpose of the present study was to evaluate plasma levels of BDNF of leprosy patients at different stages of multidrug therapy (MDT) in comparison with non-infected individuals. Plasma levels of BDNF were measured by ELISA in 30 healthy controls and 37 leprosy patients at diagnosis, during and after MDT. Plasma levels of BDNF tended to be higher in control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…As regards the operational classification and gender, a greater number of multibacillary cases were found in men, which runs in line with findings from Costa, 20 Barbosa et al, 21 and Moschioni. 22 The multibacillary form is a signal that the disease received a late diagnosis, thus favoring the maintenance of the transmission chain, given that it is considered to be the main means of disease transmission.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As regards the operational classification and gender, a greater number of multibacillary cases were found in men, which runs in line with findings from Costa, 20 Barbosa et al, 21 and Moschioni. 22 The multibacillary form is a signal that the disease received a late diagnosis, thus favoring the maintenance of the transmission chain, given that it is considered to be the main means of disease transmission.…”
Section: Discussionsupporting
confidence: 88%
“…19 Hence, biological and economic factors, and especially differences in the sociocultural behavior between the genders, may well be related to the greater detection of cases in the male population. 20 …”
Section: Discussionmentioning
confidence: 99%
“…In spite of antibodies against NGF have also been implicated as indicators of leprosy neuritic status 27 , serological data in our study did not demonstrate any differences between leprosy and control serum samples concerning circulating neurotrophins, suggesting that it is not a representative method to evaluate neural damage in non-reactional leprosy. In accordance, Costa et al 28 did not find differences in BDNF serum levels in healthy control and leprosy patients before, during and after multidrug therapy. We also investigated alterations in clinical parameters, such as loss of protective sensitivity, and its possible correlation with tissue expression of neurotrophins.…”
Section: Discussionsupporting
confidence: 77%
“…(12) One study demonstrated that BDNF levels tend to be lower in leprosy patients than in healthy individuals, which might reflect how MLinfection triggers the loss of neurotrophic stimulus by BDNF downregulation. (13) The therapeutic implications in neurotrophins regulation on the myelination program of the peripheral nervous system may be extended to demyelinating peripheral neuropathies, including leprosy, and nerve injury. (14) Given the significant role of neurotrophins on neural homeostasis and recovery after injury, we aimed to investigate the effect of ML on neurotrophins expression in human SC and mice sciatic nerves to better understand their role in leprosy neuropathy, and aiming to contribute to future therapeutic approaches.…”
mentioning
confidence: 99%
“… 12 One study demonstrated that BDNF levels tend to be lower in leprosy patients than in healthy individuals, which might reflect how ML-infection triggers the loss of neurotrophic stimulus by BDNF downregulation. 13 …”
mentioning
confidence: 99%